Peningkatan Keaktifan Belajar Siswa pada Mata Pelajaran Matematika melalui Metode Make a Match Siswa Kelas V Sekolah Dasar - Saputri, Oktaviana; Utomo, Arief Cahyo (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
Application of the Make a Match learning method using paired cards containing questions and answers to increase students' active learning. The purpose of this study is to explain how the Make a Match learning approach is used to improve class V students' active learning in mathematics classes at SD N Trangsan 1. Class action research (PTK) is employed in this study. Planning, action, observation, and reflection are the four steps in each cycle of the Kemmis & McTaggart model that is being used. 17 students participated in the two rounds of this research in class V. Tests (formative tests) and non-tests (observations) were used to gather data. Based on the findings of the study activities conducted in the classroom, it can be said that the Make a Match approach to learning can boost students' engagement in mathematics. The average learning activity at SD N Trangsan 1 increased, namely in the pre-cycle 49,93% (very poor category), in cycle 1 it was 69,33% (enough category). After improvements were made from cycle 1 reflection, student learning activity in cycle II increased to 86,66% (very good category).